Etika Guru dan Murid dalam Pendidikan Perspektif Imam Al-Ghazali - Ijah Khadijah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
TEACHER AND STUDENT ETHICS IN EDUCATION OF IMAM AL-GHAZALI'S PERSPECTIVE. Humans in general in overcoming all weaknesses are by preparing the next generation through religious education and teaching as well as worldly knowledge both formally and informally. education should be rooted in the problems that are around us. The problem that I think is currently being faced is the decline in ethos in social relations both between individuals and between groups, or individuals with groups. Ethics is a very important crown that we need to uphold, the pattern of relations between teachers and students is something very vital . This study concluded that 1) Ethics is seen as something sacred that must exist and be owned by everyone, especially the ethics of teachers and students. 2) Understanding the ethics of teachers and students in the teaching and learning process according to Al-Ghazali concluded that education is essentially the interaction between educators and students. 3) The ethics of teachers and students can be reflected in the gentle attitude and compassion the teacher aims to draw closer to God.